The capability of early detection of eye diseases in the community by primary health facility worker - Doni Widyandana; Muhammad Eko Prayogo; Suhardjo Suhardjo (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
Cataract is one of the biggest causes of blindness in the world. As many as 2.4 million people suffered from cataracts in Indonesia in 2013. Therefore, early detection needs to be done to prevent further complications. However, health workers' limited ability in primary health care facilities has resulted in high cataract diagnosis rates. The purpose of this study was to determine the ability of early detection of eye diseases, especially cataracts by primary health care workers. This study was conducted using a quantitative descriptive method analyzing 158 medical records as a result of early detection of primary health care facilities in Sleman Regency, which were sent to the ophthalmologist team of the Department of Eye Health FKKMK UGM to be re-examined. The re-examination results by a team of ophthalmologists received 141 medical records that fulfilled the inclusion criteria, consisting of 61 patients confirmed by cataract diagnosis (43.3%) and 80 patients with a diagnosis of not cataract (56.7%). According to the study, primary health care workers' ability towards early detection of cataracts in Sleman Regency needed to be enhanced (4.3%).